Certolizumab pegol in the treatment of Takayasu arteritis - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2018)
Objectives. Certolizumab pegol (CZP) is a PEGylated antigen-binding fragment-fragment of a humanized mAb neutralizing TNF. It lacks Fc-fragment and has a very low potential to cross the placenta. We aimed to report the efficacy and safety of CZP in a case series of patients with refractory Takayasu arteritis (TA). Methods. Ten females of reproductive age (18-35 years) with TA were treated with CZP (at a dose of 400 mg at weeks 0, 2 and 4 and at 200 mg every 2 weeks thereafter) for a median of 10 months (range 3-28). Prior to CZP administration all patients received glucocorticoids and +/- MTX, CYC, AZA, HCQ, LEF or MMF. Six patients were previously treated with other biological anti-cytokine drugs. The National Institutes of Health criteria and the Indian Takayasu Clinical Activity Score 2010 were used to define disease activity. Results. All patients rapidly responded to treatment with CZP and were able to taper prednisone and MTX doses. Treatment with CZP resulted in a significant decrease in median serum CRP levels and normalization of Indian Takayasu Clinical Activity Score 2010 score in 9 of 10 patients. Remission of systemic vasculitis was achieved in all patients. Seven patients maintained remission for at least 4 months, while one patient developed relapse after 2 years of CZP treatment. Side effects included mild infections (n = 5). Conclusion. Our case series suggests that CZP may be an effective and steroid-sparing treatment option in patients with active TA even if they did not previously respond to other TNF inhibitors or tocilizumab.
Keywords: TNF inhibitors; certolizumab pegol; Takayasu arteritis; ANTIRHEUMATIC DRUGS; CASES SERIES; MULTICENTER; PREGNANCY; INHIBITORS; INFLIXIMAB; EFFICACY; CRITERIA; STANDARD; ALPHA